Localization principles for Schrödinger operator with a singular matrix potential - Mikhailets, V. A.; Murach, A. A.; Novikov, V. (Methods of Functional Analysis and Topology, 2017)
We study the spectrum of the one-dimensional Schrödinger operator H_0 with a matrix singular distributional potential q=Q’ where QL^2_loc (R,C^m). We obtain generalizations of Ismagilov’s localization principles, which give necessary and sufficient conditions for the spectrum of H_0 to be bounded below and discrete.